Misbehaving: The Making of Behavioral Economics by Richard H. Thaler: Critical Evaluation & Review - Turkiah Alotibi (Journal of Economics and Behavioral Studies, 2022)
Thaler's ability for writing has resulted in a book that is a mix of his experiences as a faculty member, anecdotes from other economists he encountered along the journey, and a background in Behavioral Economics. Richard Thaler provides an analysis of how subjective factors influence decision-making in matters related to the economy and personal finances. The subject of "Misbehaving" is one of dominance and special interests; its power that economists were refusing and defending against the possibility of being irrational. Reading "Misbehaving" is recommended for those who want to understand how psychology influences decision-making with money and the economy, and for those who want to understand Behavioral Economics. This review will look further into evaluating the concept of irrationality and decision-making in behavioral economics.